Responding to the emergence of antifungal drug resistance: perspectives from the bench and the bedside. (August 2018) - Beardsley, Justin; Halliday, Catriona L; Chen, Sharon C-A; Sorrell, Tania C
The incidence of serious fungal infections is increasing rapidly, and yet the rate of new drugs becoming available to treat them is slow. The limited therapeutic armamentarium is a challenge for clinicians, because the available drugs are often toxic, expensive, difficult to administer, ineffective or a combination of all four. Given this setting, the emergence of resistance is especially concerning, and a review of the topic is timely. Here we discuss antifungal drug resistance in Candida spp. and Aspergillus spp. with reference to the most commonly used first-line antifungal agents – azoles and echinocandins. We review the resistance mechanisms of the leading pathogens, how resistance can be identified in the diagnostic lab and the clinical implications of resistance once detected.